Correlation between higher-order thinking skills and level of intelligence with scientific literacy on junior high school students - Yuriza, Putri Emilia; Adisyahputra, A; Sigit, Diana Vivanti (Biosfer: Jurnal Pendidikan Biologi, 2018)
Scientific literacy is the major purpose in learning science for 15 year-old students before they learn science in separated field such as physics, biology, and chemistry. The aim of this research was to determine the correlation between higher-order thinking skillS and level of intelligence with scientific literacy on junior high school students. This research involved 189 students grade IX in East Jakarta as the samples. The method used in this research was descriptive quantitative and using multiple correlation to test the hypothesis. The writer collected the data by utilizing PISA 2009’s scientific literacy test and Kamalia 2011’s higher order thinking skills test. Research hypothesis tested by Pearson Product Moment correlation with α=0,05. Coefficient of correlation was 0,350, it means that there was positive correlation between comprehension reading skill, higher-order thinking skill, and level of intelligence with scientific literacy on junior high school students